Dabigatran-induced Vasculitis on the Palms: A Case Report and Review of Literature - Snehal Balvant Lunge; Anisha P Bindagi (Clinical Dermatology Review)
Dabigatran is one of the newer nonvitamin K antagonist oral anticoagulants and has been approved for atrial fibrillation and prevention of venous thromboembolism. Till date, very few cases of dabigatran-induced leukocytoclastic vasculitis (LCV), also known as hypersensitivity vasculitis or hypersensitivity angiitis, have been described in the literature. We present the case of a 50-year-old male with deep vein thrombosis who developed palpable purpura and petechiae over the palms after dabigatran initiation. The present case highlights dabigatran as a potential risk for LCV, the rare site of LCV over the palms, and also provides insight into management and further evaluation.